Sacred assemblies and civic engagement: how religion matters for America's newest immigrants - Kniss, Fred Lamar (Rutgers University Press, 2007)
Introduction -- Purity and protest : sectarianism and immigrant civic engagement -- Locating the moral authority of immigrant congregations -- The moral projects of immigrant congregations -- "Making it in America" : occupational and economic adaptation in immigrant congregations -- Religion, education, and civic tensions in immigrant congregations -- Marriage patterns in immigrant congregations : implications for social distance and group identity -- Language in immigrant congregations : religious and civic considerations -- Individual engagement : citizenship in immigrant religions -- Organizational engagement : the ecology of immigrant congregations -- When and how religion matters for immigrant civic engagement